In vitro fosfomycin activity in vancomycin-resistant Enterococcus faecalis - Superti,Silvana (2009)
Enterococci are part of the endogenous flora of human beings, are naturally resistant to several classes of antimicrobials, and are able to acquire resistance with relative ease. Currently the vancomycin-resistant enterococci are spread all over the world and treatment options for infections caused by it are often extremely limited. We assessed 193 vancomycin-resistant Enterococcus faecalis isolates collected from four different hospitals in Porto Alegre for their susceptibility to fosfomycin using the E-test and agar diffusion. Fosfomycin proved to be active in vitro against the great majority of isolates, indicating that it is a valid option in the treatment of these infections.